2017
DOI: 10.1192/bjp.bp.117.201418
|View full text |Cite
|
Sign up to set email alerts
|

Depressive and anxious symptoms and the risk of secondary school non-completion

Abstract: Evidence regarding the association between adolescent internalising symptoms and school non-completion has been limited and inconclusive.To examine whether depressive and anxious symptoms at secondary school entry predict school non-completion beyond confounders and whether associations differ by baseline academic functioning.We used logistic regression to examine associations between depressive and anxious symptoms in grade 7 (age 12-14) and school non-completion (age 18-20) in 4962 adolescents.Depressive sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Attention-deficit hyperactivity disorder (ADHD) predicts lower educational attainment, as measured by test scores and grade repetition [9][10][11] , including where sibling-fixed effects are used to control for family-level confounding 10 . Evidence is more mixed for depressive symptoms 6,[12][13][14][15][16] , which in some studies show a negative association with years of schooling but in others do not. For autism spectum disorder (ASD), evidence suggests substantial heterogeneity in educational outcomes, even after considering variability in IQ 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Attention-deficit hyperactivity disorder (ADHD) predicts lower educational attainment, as measured by test scores and grade repetition [9][10][11] , including where sibling-fixed effects are used to control for family-level confounding 10 . Evidence is more mixed for depressive symptoms 6,[12][13][14][15][16] , which in some studies show a negative association with years of schooling but in others do not. For autism spectum disorder (ASD), evidence suggests substantial heterogeneity in educational outcomes, even after considering variability in IQ 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…These results are in line with previous investigations of childhood‐onset conduct problems (Darney et al, 2013; Jimerson et al, 2002; Vitaro et al, 2001). However, as depressive symptoms did not significantly predict the risk of dropout, it may be that only depressive symptoms in later years affect dropout, as studies that have found this link have only tested youth in sixth grade or higher (Brière et al, 2017; Fergusson & Woodward, 2002; Fletcher, 2010; Fortin et al, 2013; Quiroga et al, 2013). By examining the effect of depressive symptoms in younger children, our study furthered existing knowledge of the prediction of dropout and is in line with studies that suggest that the timing of depression matters (e.g., Dupéré et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Investigations by researchers in the United States and Canada have linked depressive symptoms in sixth and seventh grade (ages 11–13) to a higher risk of dropout by the end of high school (Fletcher, 2010; Fortin et al, 2013; Orpinas et al, 2015; Quiroga et al, 2013). Other studies have only found a link between depressive symptoms and dropout for subgroups of students (Brière et al, 2017; Dupéré et al, 2018), while others have found no significant association (Gubbels et al, 2019). Brière et al (2017) only found a link between depressive symptoms in ages 12–14 and school dropout by adulthood for students who had higher academic achievement than the average at the start of their secondary studies.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations